The impact of the Cyprus comprehensive smoking ban on air quality and economic business of hospitality venues - Christophi Costas A; Paisi Martha; Pampaka Despina; Kehagias Martha; Vardavas Constantine; Connolly Gregory N (BMC, 2013)
Abstract Background Several countries, including Cyprus, have passed smoke-free legislations in recent years. The goal of this study was to assess the indoor levels of particulate matter in hospitality venues in Cyprus before and after the implementation of the law on 1/1/2010, evaluate the role of enforcement, and examine the legislation's effect on revenue and employment. Methods Several hospitality venues (n = 35) were sampled between April 2007 and January 2008, and 21 of those were re-sampled after the introduction of the smoking ban, between March and May 2010. Data on enforcement was provided by the Cyprus Police whereas data on revenue and employment within the hospitality industry of Cyprus were obtained from the Cyprus Statistical Service; comparisons were made between the corresponding figures before and after the implementation of the law. Results The median level of PM2.5 associated with secondhand smoking was 161 μg/m3 pre-ban and dropped to 3 μg/m3 post-ban (98% decrease, p < 0.0001). Furthermore, in the year following the ban, the hotel turnover rate increased by 4.1% and the restaurant revenue by 6.4%; employment increased that same year by 7.2% and 1.0%, respectively. Conclusion Smoke free legislations, when enforced, are highly effective in improving the air quality and reducing the levels of indoor PM2.5. Strict enforcement plays a key role in the successful implementation of smoking bans. Even in nations with high smoking prevalence comprehensive smoking laws can be effectively implemented and have no negative effect on accommodation, food, and beverage services.